The influence of self-efficacy on learning outcomes mathematics: Mediated motivation to learn mathematics - Syahraini, Nur; Syawahid, M; Nugraha, Yandika (Mahesa Research Center, 2025)
This study seeks to elucidate the impact of self-efficacy on learning motivation and mathematics learning outcomes of seventh-grade students enrolled at a school in Mataram City. Furthermore, it explores the role of learning motivation as a mediating variable in this relationship. Employing a quantitative approach with a correlational design, the study sample comprises 168 individuals, selected through a simple random sampling technique. Data was collected via a questionnaire assessing self-efficacy, learning motivation, and mid-term test scores. The path analysis revealed that self-efficacy exhibited a positive and statistically significant influence on both learning motivation (86.8%) and learning outcomes (21.9%). Conversely, learning motivation did not demonstrate a significant impact on learning outcomes (7.6%) nor did it mediate the association between self-efficacy and learning outcomes. This study underscores the paramount significance of self-efficacy in fostering learning motivation. While increased motivation may not directly translate into enhanced learning outcomes, it necessitates the implementation of more effective learning strategies and teacher support to augment student achievement.